2011
DOI: 10.1007/s10336-011-0714-1
|View full text |Cite
|
Sign up to set email alerts
|

Intersexual differences in the diving behaviour of Imperial Cormorants

Abstract: Intersexual differences in the foraging behaviour have been examined in several seabird species, especially those exhibiting sexual size dimorphism. We studied intersex behavioural differences in the Imperial Cormorant (Phalacrocorax atriceps), a size dimorphic seabird. Twenty adults (11 females and 9 males), breeding at Punta León (43°04 0 S; 64°2 0 W), Chubut, Argentina, were equipped with loggers to measure tri-axial acceleration and depth, to calculate the foraging trip time/activity budgets and diving beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Shepard et al 2009, Cook et al 2012 should have increasing bottom durations (e.g. Wilson et al 2011, Gómez-Laich et al 2012. However (second process), as total dive durations in crease, animals have to spend disproportionately longer periods at the surface recovering from dives (e.g.…”
Section: Effect Of Attached Devices On the Foraging Of Birdsmentioning
confidence: 99%
“…Shepard et al 2009, Cook et al 2012 should have increasing bottom durations (e.g. Wilson et al 2011, Gómez-Laich et al 2012. However (second process), as total dive durations in crease, animals have to spend disproportionately longer periods at the surface recovering from dives (e.g.…”
Section: Effect Of Attached Devices On the Foraging Of Birdsmentioning
confidence: 99%
“…It seems plausible that males hunting in the late afternoon when whitefish already commence their ascent are likely to catch this species at Chiemsee. Furthermore, males diving deeper than females have been reported for other cormorant species (e.g., Gomez Laich et al., ; Watanuki et al., ); this could make whitefish in the Alpine foreland even better accessible for males.…”
Section: Discussionmentioning
confidence: 86%
“…In many studies, this might mean that just the coarse‐scale behaviors need to be identified; for example, when comparing time‐activity budgets between individuals or groups (Gómez Laich et al. ; Le Vaillant et al. ) or for isolating certain behaviors to calculate associated energetic costs (Wilson et al.…”
Section: Introductionmentioning
confidence: 99%